2020
DOI: 10.1155/2020/5135893
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Uncoupling Protein 2 Enhances the Radiosensitivity of Cervical Cancer Cells by Promoting the Production of Reactive Oxygen Species

Abstract: Objective. The mechanism of enhanced radiosensitivity induced by mitochondrial uncoupling protein UCP2 was investigated in HeLa cells to provide a theoretical basis as a novel target for cervical cancer treatment. Methods. HeLa cells were irradiated with 4 Gy X-radiation at 1.0 Gy/min. The expression of UCP2 mRNA and protein was assayed by real-time quantitative polymerase chain reaction and western blotting. UCP2 siRNA and negative control siRNA fragments were constructed and transfected into HeLa cells 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Genes involved in migration, cell proliferation, cell invasion, tumor metastasis, and EMT were significantly upregulated in the PD group (e.g., MDC1, UCP2, RBM45, BCL9L, P2RX6, RER1, EFNA2, CASK, CERCAM, and PTPRN). Interestingly, MDC1 has been reported as a key regulator of the DNA damage response in higher eukaryotes [ 26 ], and UCP2 and RBM45 have been implicated in RT resistance [ 27 , 28 ]. Among the top 100 genes, there was a class of genes related to a ubiquitination proteasome hydrolysis system, such as RBM45, TRIM9, PTPRN, RNF123, RNF220, and DTX1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes involved in migration, cell proliferation, cell invasion, tumor metastasis, and EMT were significantly upregulated in the PD group (e.g., MDC1, UCP2, RBM45, BCL9L, P2RX6, RER1, EFNA2, CASK, CERCAM, and PTPRN). Interestingly, MDC1 has been reported as a key regulator of the DNA damage response in higher eukaryotes [ 26 ], and UCP2 and RBM45 have been implicated in RT resistance [ 27 , 28 ]. Among the top 100 genes, there was a class of genes related to a ubiquitination proteasome hydrolysis system, such as RBM45, TRIM9, PTPRN, RNF123, RNF220, and DTX1.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified the differentially expressed genes between RT responder and nonresponder. Among them, MDC1 [ 26 ], UCP2 [ 27 ], and RBM45 [ 28 ] have been demonstrated to be involved in the DNA damage pathway and radiosensitivity. MDC1 [ 26 ] was identified as a component of DNA repair complex, controlling the damage-induced cell cycle arrest checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that UCPs are involved in tumor progression, remodeling tumor microenvironment [ 7 ], chemoresistance [ 23 ] and survival of cancer patients [ 24 ]. Given the functional significance of UCPs in cancer, several studies suggested that UCPs might be a reliable marker for predicting prognoses of tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that UCPs are involved in tumor progression, remodeling tumor microenvironment [23], chemoresistance [24] and survival of cancer patients [25]. Given the functional signi cance of UCPs in cancer, several studies suggested that UCPs might be a reliable marker for predicting prognoses of tumor patients.…”
Section: Discussionmentioning
confidence: 99%